Theoretical framework of critical success factors (CSFs) for Business Intelligence (BI) System - Magaireah A.I.; Sulaiman H.; Ali N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bismuth; Competitive intelligence; Business intelligence systems; Critical success factor; CSFs; Organizational factors; Organizational structures; Theoretical foundations; Theoretical framework; theoritical framework; Information analysis